Comparison of methane, nitrous oxide fluxes and CO2 respiration rates from a Mediterranean cork oak ecosystem and improved pasture - Shvaleva, Alla; e Silva, Filipe; Costa, Joaquim Miguel; Correia, Alexandra; Anderson, Margaret; Lobo-do-Vale, Raquel; Fangueiro, David; Bicho, Catarina; Pereira, Joo Santos; Chaves, Maria Manuela; Skiba, Ute; Cruz, Cristina (PLANT AND SOIL, 2014)
During the recent decades, cork oak (Q. suber) mortality has been increasing in Mediterranean oak woodland endangering the economical and environmental sustainability of the ``montado{''} ecosystem. This fact in combination with climate change and conversion of forestland to pasture may significantly affect the soil-atmosphere greenhouse gases (GHGs) exchange. Our study evaluates the impact of oak trees as compared to pasture on net ecosystem GHG (CH4, N2O, and CO2) exchange as well as the main environmental factors influencing this exchange. We used field chamber measurements for the collection of GHGs under three different conditions: 1) open area (OA), 2) under tree canopy area (UC) and 3) improved pasture (IP). Experiments were done under typical Mediterranean climate at central Portugal in 2010 and 2011. The UC had higher nitrification potential, soil C/N ratio, electrical conductivity, litter input and soil organic matter (SOM) than OA and IP. SOM positively correlated with soil CH4 and N2O fluxes but not with soil CO2 respiration rates. Soil water content (SWC) drives both CH4 and N2O fluxes. Under certain conditions, when SWC reached a threshold (7 % for CH4 and 3 % for N2O) the result was net uptake and that net uptake increased with SWC. This was the case for the UC and OA. Conversely, for the IP soil water content above 4 % promoted net CH4 release. Our results show that cork oak influences soil properties and consequently GHGs fluxes. In the UC the input of litter for SOM together with soil moisture, favoured microbiological activity and related GHGs fluxes. Soil temperature is a secondary factor in the studied conditions. Our results also emphasized the potential impact posed by decreased cork oak tree density in the functioning of the ``montado{''} ecosystem.
Keywords: evergreen oak; Greenhouse gases; litter; Mediterranean; organic matter; Root density

Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz; Lobo-do-Vale, Raquel; Rodrigues, Maria Lucília; Almeida, Pedro; Herd, Alastair; Grant, Olga Mary; David, Teresa Soares; Schmidt, Markus; Otieno, Denis; Keenan, Trevor F.; Gouveia, Célia; Mériaux, Catherine; et al. (Agricultural and Forest Meteorology, 2014)
This study details the physiological responses of cork oak (Quercus suber L.) to manipulated water inputs. Treatments named as dry, ambient and wet, which received 80, 100 and 120% of the annual precipitation, respectively, were applied to a Mediterranean woodland in southern Portugal. Tree ecophysiology and growth were monitored from 2003 to 2005. The impacts of the water manipulation were primarily observed in tree transpiration, especially dur- ing summer drought. Rainfall exclusion reduced the annual stand canopy transpiration by 10% over the 2-year study period, while irrigation increased it by 11%. The accumulated tree transpiration matched precipitation in spring 2004 and 2005 at the stand level, suggesting that cork oak trees rely on precip- itation water sources during the peak of the growing season. However, during the summer droughts, by trees appeared unaffected by the extreme drought of 2005. Our study shows that cork oak rapidly and completely recovered from the extreme dry year of 2005 or from rainfall exclusion. Our results support the eco-hydrological equilibrium theory by which plant acquire complementary protective mechanisms to buffer the large variability in water availability experienced in semi-arid ecosystems. In optimizing their structural biomass increase in response to increasing drought stress, cork oak trees succeeded in restricting water losses to maintain the minimum leaf water potential above the critical threshold of xylem embolism, though with narrower hydraulic safety margins in 2005. Our findings highlight cork oak’s sensitivity to the amount and timing of late spring precipitation. This could be critical as future climate scenarios predict a reduction of spring precipitation as well as enhanced severity of droughts in the Iberian Peninsula by the end of the 21st century. In inducing water stress before the onset of summer droughts, the predicted spring precipitation decline could drive the species closer to the threshold of catastrophic xylem embolism at the peak of the drought period. groundwater was the main water source for trees. Despite the significant differences in soil water content and tree transpiration, no treatment effects could be detected in leaf water potential and leaf gas exchange, except for a single event after spring irri- gations in the very dry year 2005. These irrigations were intentionally delayed to reduce dry spell duration during the peak of tree growing season. They resulted in an acute positive physiological response of trees from the wet treatment one week after the last irrigation event leading to a 32% raise of stem diame- ter increment the following months. Our results suggest that in a semi-arid environment precipitation changes in spring (amount and timing) have a stronger impact on cork oak physiology and growth than an overall change in the total annual precipitation. The extreme drought of 2005 had a negative impact on tree growth. The annual increment of tree trunk diameter in the ambient and dry treatments was reduced, while it increased for trees from the wet treatment. Water shortage also significantly reduced leaf area. The latter dropped by 10.4% in response to the extreme drought of 2005 in trees from the ambient treatment. The reduction was less pronounced in trees of the wet treatment (−7.6%), and more pronounced in trees of the dry treatment (−14.7%). Cork oak showed high resiliency to inter-annual precipitation variability. The annual accumulated tree transpiration, the minimum midday leaf water potential and the absolute amount of groundwater used
From Duplicate 1 ( Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz; Lobo-do-Vale, Raquel; Rodrigues, Maria Lucília; Almeida, Pedro; Herd, Alastair; Grant, Olga Mary; David, Teresa Soares; Schmidt, Markus; Otieno, Denis; Keenan, Trevor F; Gouveia, Célia; Mériaux, Catherine; Chaves, Maria Manuela; Pereira, João S )From Duplicate 1 ( Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz; Lobo-do-Vale, Raquel; Rodrigues, Maria Lucília; Almeida, Pedro; Herd, Alastair; Grant, Olga Mary; David, Teresa Soares; Schmidt, Markus; Otieno, Denis; Keenan, Trevor F; Gouveia, Célia; Mériaux, Catherine; Chaves, Maria Manuela; Pereira, João S )The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Gas exchange; Precipitation change; Quercus suber; Soil moisture; Throughfall manipulation; Tree transpiration